Early intervention for inhibited young children: a randomized controlled trial comparing the Turtle Program and Cool Little Kids. (29th June 2021) - Chronis‐Tuscano, Andrea; Novick, Danielle R.; Danko, Christina M.; Smith, Kelly A.; Wagner, Nicholas J.; Wang, Christine H.; Druskin, Lindsay; Dougherty, Lea R.; Rubin, Kenneth H.
Abstract : Background: Children classified as behaviorally inhibited (BI) are at risk for social anxiety. Risk for anxiety is moderated by both parental behavior and social–emotional competence. Grounded in developmental–transactional theory, the Turtle Program involves both parent and child treatment components delivered within the peer context. Our pilot work demonstrated beneficial effects of the Turtle Program ('Turtle') over a waitlist control group. Herein, we report results of a rigorous randomized controlled trial (RCT) comparing Turtle to the best available treatment for young children high in BI, Cool Little Kids (CLK). Methods: One hundred and fifty‐one parents and their 3.5‐ to 5‐year‐old children selected on the basis of BI were randomly assigned to Turtle or CLK, delivered in group format over 8 weeks. Effects on child anxiety, life interference, BI, and observed parenting were examined at post‐treatment and 1‐year follow‐up. ClinicalTrials.gov registration: NCT02308826. Results: No significant main effect differences were found between Turtle and CLK on child anxiety; children in both programs evidenced significant improvements in BI, anxiety severity, family accommodation, and child impairment. However, Turtle yielded increased observed warm/engaged parenting and decreased observed negative control, compared with CLK. Parental social anxiety moderated effects; parents with higher anxiety demonstrated diminished improvements in child impairment, and parent accommodation in CLK, but not in Turtle. Children of parents with higher anxiety demonstrated more improvements in child BI in Turtle, but not in CLK. Conclusions: Turtle and CLK are both effective early interventions for young children with BI. Turtle is more effective in improving parenting behaviors associated with the development and maintenance of child anxiety. Turtle also proved to be more effective than CLK for parents with social anxiety. Results suggest that Turtle should be recommended when parents have social anxiety; however, in the absence of parent anxiety, CLK may offer a more efficient treatment model.